Association of middle cerebral artery aneurysms and variation of the A1 segment - Xiaohui Li; Xi Yue; Zhengyuan Xie; Lina Nie; Ge Huang; Yilong Peng; Jiyong Gu; Chan Lai; Hongzhi Gao (PLoS ONE, 2025)
Objective The disturbance of blood flow caused by variations in the circle of Willis is an important factor in the occurrence and development of aneurysms. Previous studies have confirmed that a fetal-type posterior cerebral artery(PCA) is closely related to posterior communicating artery (PcoA) aneurysms, while anatomical variations of the anterior cerebral artery (ACA) appear to correlate with the prevalence of aneurysms in the anterior communicating artery (ACoA). However, the relationship between variations in the circle of Willis and middle cerebral artery(MCA) aneurysms remains controversial. Methods This study retrospectively analyzed the Computed Tomography Angiography (CTA) data of 269 cases of patients with intracranial aneurysms and 269 cases of patients without aneurysms at the Jiangmen Central Hospital from January 2012 to December 2023. The 3D-Slicer software was utilized to measure the artery diameter and investigate the relationship between anatomical variations of the circle of Willis and MCA aneurysm. Results In the aneurysm group, there were 39 cases of A1 dysplasia on the affected side, compared to 20 cases in the control group, with a significantly higher prevalence in the aneurysm group (P = 0.0125). The average diameter of middle cerebral arteries was smaller in the aneurysm group (2.304 ± 0.5613 mm) than in the control group (2.611 ± 0.5500 mm), showing a significant difference (P = 0.001).In aneurysm patients, the MCA diameter on the affected side was smaller in the A1 dysplasia group (2.156 ± 0.5256mm) compared to the A1 normal development group (2.405 ± 0.5718mm, P = 0.0114). Additionally, the average maximum aneurysm diameter was larger in the A1 dysplasia group (6.958 ± 5.163mm) than in the A1 normal development group (5.483 ± 3.336mm, P = 0.03).The presence of ipsilateral A1 dysplasia had a statistically significant effect on the occurrence and rupture of MCA aneurysms. Conclusions The variation in the circle of Willis may impact the occurrence and rupture of MCA aneurysms by altering blood flow distribution, constricting the diameter of the parent artery, and shifting the location of blood flow impact.